Screening for infertility‐related stress at the time of initial infertility consultation: psychometric properties of a brief measure. (15th October 2015) - Casu, Giulia; Gremigni, Paola
Abstract: Aim: To develop and psychometrically test a brief self‐report to assess the amount of infertility‐related stress; to investigate how infertility‐related stress was associated to socio‐demographics, causes of infertility and emotional distress. Background: Infertility exerts a stress effect on both personal and interpersonal areas. Due to the burden of multiple assessments in fertility clinics, there is the need for very brief and easy to administer measures of the stressful impact of infertility on the intrapersonal and interpersonal life domains. Design: The study had a psychometric, cross‐sectional design. Method: Between January ‐ December 2013, a total of 597 Italian infertile patients (58·6% women), recruited at the time of initial infertility consultation, completed the Infertility‐Related Stress Scale. A subsample of 200 participants (50% women) also completed self‐reports of anxiety and depression. A subsample of 40 patients completed again the Infertility‐Related Stress Scale at a 4‐week follow‐up visit. Results: Confirmatory factor analyses supported the proposed two‐factor model of infertility stress affecting intrapersonal and interpersonal life domains. Both dimensions showed good reliability and were associated in expected ways with emotional distress. Patients with above‐threshold levels of anxiety and depression showed higher infertility stress in both domains and particularly in the intrapersonal area. Infertility stress was significantly higher in women than in men in the intrapersonal domain. Conclusion: The Infertility‐Related Stress Scale showed evidence of validity and reliability. This new, brief self‐report can assist fertility clinic staff in identifying those patients who need support to overcome the stressful impact of infertility on intrapersonal and interpersonal domains.